Networks of Opportunity: Unpacking the Role of Family, Peers, and Community in Shaping Economic Mobility in Low-Income Urban Settings - Shahzeb Danish; Insha; Fizza; Laiba; Tayaba Mahmood; Ahmed Usman; Fouzia Sadaf (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2024)
This paper examines the role of social networks, specifically family, peers, and community, in influencing economic mobility in low-income urban areas, where access to opportunities is often constrained by education, employment, and social connections. Drawing on both qualitative interviews and survey data, the study investigates how the structure and dynamics of social capital enable or hinder individuals’ access to key resources for education, employment, and mentorship. The findings highlight the dual nature of family structures, where intergenerational support can either serve as a pathway to economic mobility or function as a mechanism of exclusion. Additionally, peer networks and community ties are explored to understand how informal channels, such as employment referrals and social support, contribute to financial success and mobility. The paper also critically examines the intersections of race, gender, and social class, revealing how these factors can exacerbate or limit individuals’ ability to leverage social capital for improved economic standing. By analyzing these dynamics, this study underscores the significant role of social capital in shaping economic outcomes and offers policy recommendations for fostering community-based approaches that open avenues for economic opportunities. Ultimately, the research illustrates how social networks, whether through support or exclusion, can either perpetuate or mitigate poverty, depending on the unequal distribution of resources within urban environments